The role and discourse of FinTech companies in ESG issues: A cross-company content analysis - Zhang, Jie (Edelweiss Applied Science and Technology, 2025)
As environmental, social, and governance (ESG) concerns continue to influence global financial markets, the role of FinTech companies in shaping and disseminating ESG discourse has garnered growing attention. While existing research has predominantly focused on ESG disclosures from traditional financial institutions, the communication strategies of FinTech firms, entities known for their agility, digital infrastructure, and platform-based ecosystems, remain underexplored. This study investigates how leading FinTech companies engage with ESG issues through public discourse by conducting a cross-company content analysis using a corpus of official reports, corporate websites, and verified social media accounts. We develop a hybrid methodology integrating natural language processing (NLP), sentiment analysis, and topic modeling to examine the volume, orientation, and thematic composition of ESG-related communications across ten FinTech firms. Our findings reveal that, while environmental narratives are frequently highlighted, governance-related content is often underrepresented. Companies differ significantly in their discursive orientation: some emphasize technological solutions to sustainability (e.g., green infrastructure, carbon-neutral systems), whereas others focus on financial inclusivity or ethical data use. Despite these divergences, a common strategic pattern emerges, namely, the framing of ESG commitments as part of broader innovation and trust-building agendas. Furthermore, our sentiment analysis indicates a consistently positive tone across ESG topics, suggesting a performative dimension in FinTech ESG communication. We also identify the use of abstract, aspirational language in social and governance narratives, contrasting with more concrete expressions in environmental disclosures. These findings contribute to a deeper understanding of the role of digital financial actors in shaping sustainability discourses and offer actionable insights for regulators, investors, and communication strategists aiming to assess ESG transparency and authenticity in the FinTech sector. By situating ESG discourse within the broader communicative practices of FinTech firms, this study underscores the importance of not only what is communicated, but how, why, and to whom, a perspective increasingly relevant in a data-driven and reputationally sensitive digital economy.